Green aquaponic system: a project to generate community income - Shaharom Harrison, Faizah; H., Anuar; A., Ikhwanuddin; J., Ahmad; I., Zakaria; Rajaee, Amy Halimah; J., Ahmad Zawawi; M. Y., Haniff; O., Muhammad Safwan (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Aquaponics is a combination of Aquaculture and Hydroponics in a recirculating aquaculture system (RAS). Waste from fish tanks were pumped into plant growing beds and then filtered out by the plants as nutrients, after which the cleaned water is recirculated back into the fish tanks. This project is an extension project which was conducted from 2008 to 2010. It is a collaborative project between Institute of Tropical Aquaculture (AQUATROP) Universiti Malaysia Terengganu, Terengganu Department of Fisheries, Agriculture Department, a local company W.H.K Integrated Sdn Bhd and the Committee of KRT Telaga Batin. The project is currently being maintained by Committee of KRT Telaga Batin. The fish cultured was catfish (Clarias gariepinus) and vegetables grown were Chinese mustard and lettuce. In the project, 3-4” catfish fingerlings were cultured until market size that is after 4 months and the vegetables took 30-35 days before being harvested. In this current project, tilapia (Oreochromis niloticus) will be cultured with combination of Chinese mustard and lettuce because tilapia will fetch a higher price (RM8-10/kg) compared to catfish (RM3.50-5/kg). This project will be conducted by one intern graduate student and final year project students. The final year project students will be involved in the monitoring and collecting data of the water quality, plant and fish growth and hydraulics. Aquaponic system at Kg. Telaga Batin consist of four fiberglass fish tanks (1.8 L x 1. 8 W x 0.92 H m) and 24 plant growing beds (1.8 L x 0.61 W x 0.2 H m). Plants grown in the green house of size 6.1 L x 9.2 W m. An air-lift system is used to distribute the water from fish tank to the growing bed using the pressure from the blower.